Antimicrobial, anti-adherence and antibiofilm activity against Staphylococcus aureus of a 4-phenyl coumarin derivative isolated from Brazilian geopropolis. (February 2020) - da Cunha, Marcos Guilherme; de Cássia Orlandi Sardi, Janaina; Freires, Irlan Almeida; Franchin, Marcelo; Rosalen, Pedro Luiz
Abstract: The discovery of new drug candidates, especially from natural products, remains a promising approach to overcome the alarmingly high microbial resistance rates. A major 4-phenyl coumarin named cinnamoyloxy-mammeisin (CNM) isolated from stingless bee geopropolis showed interesting biological properties; however, its antimicrobial activity against Staphylococcus aureus has never been investigated. In order to clarify these properties, CNM isolated from geopropolis was initially tested against methicillin-susceptible and -resistant S. aureus strains. Further, the effects of CNM were assessed on the microbial adherence to human cells, biofilm formation and mature biofilm. Then, the acute toxicity of the compound was determined in Galleria mellonella . CNM showed bacteriostatic activity against methicillin-susceptible and -resistant S. aureus strains, with MIC of 11.3 μM. In addition, CNM at 5.7 μM reduced bacterial adherence to human keratinocytes from 1 to 3 h and disrupted biofilm formation by reducing cell viability and architecture, as evidenced by scanning electron microscopy. The acute toxicity assay indicated no significant harmful effects. Based on these findings, CNM can be considered a promising compound with anti-S. aureus properties and predicted low toxicity. Thus, it may be used as a drug candidate or lead compound for structure/activity optimization. Highlights: Cinnamoyloxy-mammeisin (CNM) has antimicrobial activity against Staphylococcus aureus. CNM showed bacteriostatic activity and reduced bacterial adherence to human keratinocytes. The acute toxicity assay indicated no significant harmful effects.